THE GLOBAL FINANCIAL CRISIS, COVID-19 AND THE RUSSIA-UKRAINE WAR: THE SAFE HAVEN POTENTIAL OF ISLAMIC ECONOMICS - Sahabuddin , Mohammad; Ahmad, Abu Umar Faruq (Bank Indonesia, 2023)
Islamic economics is an innovative phenomenon in the modern world. In many developed and developing countries, Islamic financial systems successfully work in parallel with their conventional peers. It is unfortunate that at the time when the world is suffering from a pandemic like COVID-19, the world community has witnessed a war between Russia and Ukraine that has disrupted the global economy. This study evaluates the safe-haven potential of Islamic economics to hedge against a global financial crisis, COVID-19 pandemic, and the Russia-Ukraine conflict and examines how Islamic economics has responded to this major disruption in the digital era. The published literature is reviewed to investigate the impact of major disruptive events like the global financial crisis 2008-2009, COVID-19 and the recent Russia-Ukraine conflict on the global economy. The findings also show that the global financial crisis, Covid-19, and the Russia-Ukraine war are the major events that have disrupted the paradigms of the changing process. Along with this changing process, the advancement of information technology plays a vital role in accelerating financial innovation in the digital era. Moreover, despite the major episodes, it has grown rapidly compared to the traditional counterpart. As the fastest growing part of the global economic system, Islamic economics has shown appeal to diverse investors and issuers.